Person factors and strategic processing in L2 listening comprehension: Examining the role of vocabulary size, metacognitive knowledge, self-efficacy, and strategy use. (July 2022) - Du, Guohui; Man, Deliang
Abstract: Research has shown that person factors and strategic processing are associated with L2 listening comprehension. Few studies, however, have considered to what extent person factors and strategic processing account for the variance of L2 listening comprehension. This study aims to investigate the predictive power of person factors (i.e., aural vocabulary size, listening metacognitive knowledge, and listening self-efficacy) and listening strategy use (i.e., top-down strategies and bottom-up strategies) on L2 listening comprehension. Data collected from a survey among 367 Chinese EFL undergraduate students were analyzed using a partial least squares structural equation modeling (PLS-SEM) approach. The results of the study indicate that altogether 20.9% of the variance in L2 listening comprehension could be explained by person factors and strategic processing. Aural vocabulary size and listening metacognitive knowledge were significant predictors of L2 listening comprehension whereas listening self-efficacy was not. Listening strategies were not significant predictors of L2 listening comprehension. Person factors did not indirectly predict L2 listening comprehension through listening strategies, either. Implications for listening instruction are considered.